THE CHALLENGES OF INTERNATIONAL AIR LAW PRINCIPLES IN GLOBALIZATION ERA - Kusumaningrum, Adi (Faculty of Law, Universitas Brawijaya, 2017)
The concept of stateâs sovereignty had become one of debatable issues within the international law studies during the 20th century. International air transport has always been one of the most regulated of industries of globalization. Therefore, airspace sovereignty no escape from the challenges of globalization. This regulatory system has been changing recently because of worldwide initiative that have paved the way for enhancing air transport liberalization. This is why numerous models have been hypothesized for a new (multilateral) aviation order to supersede bilateralism, which still remains the primary vehicle for liberalizing international air transport service for most states. This study intends to discuss about the basic principles of international airspace law that frequently facing challenges in the globalization era. In the last few decades is that the economic aspects of airspace sovereignty have dominated change, or the lack thereof, in the international air sovereignty regime. In addition, there are many challanges in politic and law. In the context of Indonesia airspace challanges, in the near future, it is needed to revitalize the function of the strong regulation. This can be started by re-evaluating the regulations that is continued by the arrangement of the anatomy of the setting that is comprehensive, systematic, careful, effective and also efficient based on two importance that are prosperity and security.